The Influence of the CIRC Model on the Motivation and Character of Class XI Students at SMA HKBP 2 Tarutung (International Forum of Researchers and Lecturers, 2025)
This research aims to investigate the influence of the CIRC (Cooperative Integrated Reading and Composition) Learning Model on the learning motivation and character of class XI students at SMA HKBP 2 Tarutung in the 2022/2023 academic year. The method used is a quantitative approach with an experimental design. Data was collected through a questionnaire that measured the level of learning motivation and student character before and after implementing the learning model. The results of the analysis show that there is a significant increase in learning motivation and student character after implementing the CIRC Model. These findings indicate that the use of collaborative learning models can increase student engagement and form positive character.